Electronic‐Reconstruction‐Enhanced Tunneling Conductance at Terrace Edges of Ultrathin Oxide Films. Issue 44 (12th October 2017) - Wang, Lingfei; Kim, Rokyeon; Kim, Yoonkoo; Kim, Choong H.; Hwang, Sangwoon; Cho, Myung Rae; Shin, Yeong Jae; Das, Saikat; Kim, Jeong Rae; Kalinin, Sergei V.; Kim, Miyoung; Yang, Sang Mo; et al.
Abstract: Quantum mechanical tunneling of electrons across ultrathin insulating oxide barriers has been studied extensively for decades due to its great potential in electronic‐device applications. In the few‐nanometers‐thick epitaxial oxide films, atomic‐scale structural imperfections, such as the ubiquitously existed one‐unit‐cell‐high terrace edges, can dramatically affect the tunneling probability and device performance. However, the underlying physics has not been investigated adequately. Here, taking ultrathin BaTiO3 films as a model system, an intrinsic tunneling‐conductance enhancement is reported near the terrace edges. Scanning‐probe‐microscopy results demonstrate the existence of highly conductive regions (tens of nanometers wide) near the terrace edges. First‐principles calculations suggest that the terrace‐edge geometry can trigger an electronic reconstruction, which reduces the effective tunneling barrier width locally. Furthermore, such tunneling‐conductance enhancement can be discovered in other transition metal oxides and controlled by surface‐termination engineering. The controllable electronic reconstruction can facilitate the implementation of oxide electronic devices and discovery of exotic low‐dimensional quantum phases. Abstract : Intrinsic tunneling‐conductance enhancement is discovered near the terrace edges of ultrathin BaTiO3 films. The terrace‐edge geometry can trigger an electronic reconstruction, which reduces the effective tunneling‐barrier width locally. Such tunneling‐conductance enhancement can be found in other transition metal oxides and is controlled by surface termination engineering.